Giant Hysteresis of Single‐Molecule Magnets Adsorbed on a Nonmagnetic Insulator. Issue 26 (9th May 2016) - Wäckerlin, Christian; Donati, Fabio; Singha, Aparajita; Baltic, Romana; Rusponi, Stefano; Diller, Katharina; Patthey, François; Pivetta, Marina; Lan, Yanhua; Klyatskaya, Svetlana; Ruben, Mario; Brune, Harald; et al.
Abstract : TbPc2 single‐molecule magnets adsorbed on a magnesium oxide tunnel barrier exhibit record magnetic remanence, record hysteresis opening, perfect out‐of‐plane alignment of the magnetic easy axes, and self‐assembly into a well‐ordered layer.